Markers of inflammation as risk predictors of lethal outcome in patients diagnosed with delirium - Stašević Karličić, Ivana; Stašević, Milena; Janković, Slobodan; Djukić Dejanović, Slavica; Milovanović, Srdjan (Vojnosanitetski pregled, 2017)
Background/Aim. Delirium is an acute or subacute, and most frequently reversible syndrome of higher cortical functions disturbances that is manifested as generalized disorder. If not prevented, it is associated with various adverse outcomes. The aim of this study was to determine the connection between the markers of inflammation and lethal outcome in patients diagnosed with delirium, hospitalized in the psychiatric intensive care unit. Methods. This retrospective study included 120 patients hospitalized in the psychiatric intensive care unit in whom examination of differences in inflammation markers was done. The examinees have been divided into two groups: the case group of 40 patients who died during the hospitalization, and the control group of 80 examinees who were discharged with the diagnosis Post delirium status. The following variables were taken into account: age, gender, clinical diagnosis of infection (pneumonia and urinary tract infection), laboratory parameters (total of white blood cells, granulocytes, monocytes, C-reactive protein − CRP) and type of delirium (withdrawal or organic). Results. The average age of the patients was 50.3 ± 13.1 years. The patients who survived delirium, were on the average 10.5 years younger than the deceased (p < 0.001). More than half (57.5%) of the deceased had pneumonia. There was a statistically significant correlation between pneumonia and lethal outcome in the patients with delirium (p < 0.001). The examinees with lethal outcome had significantly higher median CRP levels than the group of examinees who survived (75.6% ± 54.0 vs 30.3 ± 42.5 ng/L, p < 0.001). Conclusion. Aiming to better and more precise diagnostics of this complicated and still unclear neuropsychiatric syndrome it would be useful to consider introduction of more precise diagnostic algorithms in every unit of intensive care. That would significantly reduce the number of delirium diagnosis overlook, decrease complication of clinical features and would also reduce the unfavorable outcome rate, therefore the total cost of treatment.